Tendon regeneration: understanding tissue physiology and development to engineer functional substitutes - Gomes, Manuela E. (2015)
In recent years, research has focused more attention to tendon tissues, unveiling aspects of tendonâ s intrinsic morphology, architecture, and functionality. The pivotal role of tendons in joint mechanics and movement implies well-established natural mechanisms of action under permanent and fine-tuned adjustments to balance the forces and loadings in order to adapt to changes in the environment. Although walking, running, or standing may be simple and easily achieved mechanisms in daily activities, the complex dynamics involved challenges researchers to combine creativity and knowledge aiming at restoring tissue morphology, architecture, and ultimately tissue functionality.